(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
This research will involve the completion of an approach to the foundations of capitalism, which is done through the study of capitalism contributions given by their representatives such as Adam Smith, Cecil Pigou, and Max Weber. From a philosophical, political, social perspective, with the aim of highlighting the strengths that have these postulates, and the effect thereof on the search for alternatives that allow the progress of peoples considering man as a central axis, linked a whole system of values. Depending on the achievement of objectives in three phases of research, a first through library research originating authors of capitalism, the principles of each of the authors considered to be highlighted , in order to make a platform appear allowing further analysis and comparison of the primary ideas and what today is evident in capitalism ; in the second phase , there will be a full characterization of the companies that claim to be capitalist , for their economic, in a comprehensive analysis under various dimensions , that will draw what capitalism was , is and will be in today’s societies and the last phase, which includes product research , is displayed under the lens of the fathers of capitalism , what would today ‘s society under the philosophical , social, political and economic dimensions , achieving a kind of ideal outline under the original assumptions of capitalism.